The snakes of the flooded region of Itaparica hydroeletric dam, Northeastern Brazil: “development” based on the drowning of wildlife - Gentil Alves Pereira Filho; Frederico Gustavo Rodrigues França; Washington Luiz Silva Vieira; Arthur Felipe Ferreira de Freitas; Zenilde Moreira Borges de Morais; Gileno Antônio Araújo Xavier; Marco Antonio de Freitas; Rômulo Romeu Nóbrega Alves; Geraldo Jorge Barbosa de Moura (Check List)
The previously underestimated biodiversity of the Caatinga underwent a transformation with the emergence of new studies, intensifying interest in the biota of this complex dry forest. Studies on snakes from the Caatinga have increased recently, resulting in 112 recorded species. Contributing to this, we present a detailed list of 23 species rescued from the Itaparica reservoir implementation in the 1980s. Collected specimens are deposited in the Herpetological and Paleoherpetological Collection at the Universidade Federal Rural de Pernambuco. The recorded snake assemblage is typical of the dry Caatingas of the Sertaneja Depression. We discuss the impacts of ﬂooding and specimen relocation without adequate planning or monitoring on snake diversity. Finally, we conclude by questioning the sustainability aspects of development and interventions in nature.